2021
DOI: 10.3389/fmed.2021.655123
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Communication Between Neuronal Networks and Intestinal Epithelial Cells in Gut Inflammation and Parkinson's Disease

Abstract: Intestinal symptoms, such as nausea, vomiting, and constipation, are common in Parkinson's disease patients. These clinical signs normally appear years before the diagnosis of the neurodegenerative disease, preceding the occurrence of motor manifestations. Moreover, it is postulated that Parkinson's disease might originate in the gut, due to a response against the intestinal microbiota leading to alterations in alpha-synuclein in the intestinal autonomic nervous system. Transmission of this protein to the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 340 publications
(336 reference statements)
0
7
0
Order By: Relevance
“…The locus rs2074404 of WNT3 was previously found to be a CD (Coeliac disease) associated polymorphism ( Dubois et al, 2010 ; Franke et al, 2010 ; Amundsen et al, 2014 ). It was also shown that gut inflammation is a main pathological feature occurring in both PD and CD and this inflammation may contribute to α-synuclein aggregation ( Dzamko et al, 2017 ; Drobny et al, 2021 ). Additionally, some SNPs in genes responsible for binding bacterial metabolites and intestinal homeostasis were associated with PD ( Gorecki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The locus rs2074404 of WNT3 was previously found to be a CD (Coeliac disease) associated polymorphism ( Dubois et al, 2010 ; Franke et al, 2010 ; Amundsen et al, 2014 ). It was also shown that gut inflammation is a main pathological feature occurring in both PD and CD and this inflammation may contribute to α-synuclein aggregation ( Dzamko et al, 2017 ; Drobny et al, 2021 ). Additionally, some SNPs in genes responsible for binding bacterial metabolites and intestinal homeostasis were associated with PD ( Gorecki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate rises as a result of this illness. Many various types of bodily fluids, such as blood and tissue, as well as the beneficial bacteria that are prevalent in large bowel ecosystems, have been the primary focus of recent investigations [220][221][222][223]. The majority of studies have focused on the beneficial microorganisms that naturally occur in the colon.…”
Section: Future Concepts and Opinions Examinedmentioning
confidence: 99%
“…This coincides with a work reporting that in PD patients, activated microglia closely interact with neurons presenting α-Syn pathological accumulation [ 113 ]. Similarly, direct administration of extracellular α-Syn primes the microglia and makes them susceptible to proinflammatory environmental challenge [ 114 ], inducing intracellular signaling cascades and modulating inflammatory cytokine production [ 115 ] ( Figure 2 A). However, it should be noted that microglia can also deal with α-Syn during cell-clearing processes [ 116 ].…”
Section: Acute Versus Chronic Inflammationmentioning
confidence: 99%